2019
DOI: 10.1111/coa.13361
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility and effectiveness of a training programme in the application of a new classification of narrow‐band imaging for vocal cord leukoplakia: A multicentre study

Abstract: Objective: To analyse the application of a new narrow-band imaging (NBI) classification in the diagnosis of vocal cord leukoplakia by laryngologists with different levels of laryngoscopic experience and to explore the impact of NBI training programmes on laryngologists' identification of benign and malignant leukoplakia.Design: Prospective multicentre study. Setting: Tertiary hospitals.Participants: Sixteen laryngologists were divided into less-experienced and experienced groups and received NBI training cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In this view, Narrow Band Imaging (NBI) represents an already consolidated improvement over conventional white light endoscopy, allowing for better and earlier identification of dysplastic/neoplastic mucosal alterations (5)(6)(7)(8). However, so far, NBI-based endoscopy remains a highly operator-dependent procedure, and its standardization remains particularly challenging, even when employing simplified pattern classification schemes (9)(10)(11)(12)(13)(14). In fact, even though such bioendoscopic tools are aimed at identifying pathognomonic superficial vascular changes in forms of abnormal intrapapillary capillary loops, a relatively long learning curve and intrinsic subjectivity of subtle visual evaluations still hamper their general and widespread adoption in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, Narrow Band Imaging (NBI) represents an already consolidated improvement over conventional white light endoscopy, allowing for better and earlier identification of dysplastic/neoplastic mucosal alterations (5)(6)(7)(8). However, so far, NBI-based endoscopy remains a highly operator-dependent procedure, and its standardization remains particularly challenging, even when employing simplified pattern classification schemes (9)(10)(11)(12)(13)(14). In fact, even though such bioendoscopic tools are aimed at identifying pathognomonic superficial vascular changes in forms of abnormal intrapapillary capillary loops, a relatively long learning curve and intrinsic subjectivity of subtle visual evaluations still hamper their general and widespread adoption in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, clinical training for the new classification of vocal fold leukoplakia has a positive effect on the accurate diagnosis of vocal fold leukoplakia. To some extent, laryngologists’ clinical experience might affect the accuracy of judging intra-epithelial papillary capillary loop spots under the narrow-band imaging mode 24 . In order to increase the adoption of diagnostic classification of vocal fold leukoplakia based on narrow-band imaging, the classification ought to be simplified further to allow beginners to master the classification scheme quickly.…”
Section: Resultsmentioning
confidence: 99%
“…Schossee et al [35] reported kappa values of 0.23-0.59 when 84 NBI images of vocal folds were presented to 3 consultants for classification of 6 types of longitudinal vascular changes, with only slight differences between white light and NBI. In a recent study by Ni et al [36], white light images and NBI images of 30 cases of glottic leukoplakia were presented to 8 experienced laryngologists and 8 less experienced laryngologists. The images were rated by all the participants before and after an hour-long NBI training course that comprised basic principle of NBI technology, the Niclassification, and a suggested, new diagnostic classification for glottic leukoplakia [37].…”
Section: Discussionmentioning
confidence: 99%